Pengaruh Pemahaman Pendidikan Inklusi terhadap Kesiapan Mengajar Anak Berkebutuhan Khusus pada Calon Guru Bahasa Indonesia - Aura Meriska; Endang Aristianti Gultom; Rosenta L Situngkir; Felicia Joice Sitinjak; Anggia Puteri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to determine the effect of understanding inclusive education on the readiness to teach children with special needs (ABK) in prospective Indonesian language teachers. The research method used is quantitative research with an associative approach, using a questionnaire instrument to measure the level of understanding of inclusive education and readiness to teach ABK. The results of the study indicate that there is a significant relationship between understanding of inclusive education and readiness to teach ABK in prospective Indonesian language teachers. A comprehensive understanding of inclusive education is an important foundation in improving the pedagogical, professional, personality, and social competencies of prospective teachers. However, the survey results show that the ability to plan lessons, readiness to teach, and readiness to create ABK-friendly learning tools are still relatively low. The main challenges faced by prospective teachers are the lack of practical experience, the lack of examples of inclusive open materials, and the continuing stigma against ABK. Therefore, a strategy is needed to improve the understanding of inclusive education through curriculum integration, field experience, and the development of inclusive teaching materials so that the readiness to teach ABK in prospective Indonesian language teachers can be optimally increased.